2006
DOI: 10.1111/j.1600-0420.2006.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ageing on retinal nerve fibre layer thickness: an evaluation by scanning laser polarimetry with variable corneal compensation

Abstract: ABSTRACT.Purpose: To evaluate whether a significant age-related thinning of the retinal nerve fibre layer (RNFL) is measurable by means of scanning laser polarimetry with variable corneal compensation (GDx-VCC) in a sample of healthy eyes. Methods: A sample of 324 eyes of 324 healthy subjects (mean age 56 ± 14 years, range 21-85 years) underwent a complete ophthalmic evaluation, standard automated perimetry and RNFL scan with the GDx-VCC. Temporal-superior-nasal-inferior-temporal (TSNIT), superior and inferior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 24 publications
3
39
2
Order By: Relevance
“…Our study outcome could have been biased by a wide age range: it has been shown that RNFL thickness, as measured by first-generation SLP, decreases with age, and such finding has been confirmed by a recent study performed by means of VCC-SLP [28]. However, it must be observed that such effect is less pronounced using the last-generation device and, in addition, no relevant differences were found in our study.…”
Section: Discussioncontrasting
confidence: 54%
“…Our study outcome could have been biased by a wide age range: it has been shown that RNFL thickness, as measured by first-generation SLP, decreases with age, and such finding has been confirmed by a recent study performed by means of VCC-SLP [28]. However, it must be observed that such effect is less pronounced using the last-generation device and, in addition, no relevant differences were found in our study.…”
Section: Discussioncontrasting
confidence: 54%
“…Crosssectional studies of RNFL thickness using scanning laser polarimetry also have found a decrease in RNFL thickness with age. [9][10][11][12] The human RNFL loses approximately 5000 axons per year from birth to death, approximately 2500 per year before age 50 and 7500 per year after 50. 3 It is not surprising, then, that RNFL thickness decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…They reported an average loss of RNFL thickness of À0.70 mm/year in glaucoma progressors (based on GPA software for standard automated perimetry (SAP)) vs À0.14 mm/year in non-progressors (Po0.001), very similar to rates of change reported elsewhere by the same group (À0.65 and À0.11 mm/year, respectively). 15 Da Pozzo et al, 56 in a cross-sectional design estimated the age-related loss of RNFL thickness in 384 healthy adults and found a rate of À0.08 mm/year attributed to ageing.…”
Section: Cslomentioning
confidence: 99%